2011
DOI: 10.1017/s1743921312012690
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength observations of GRB afterglows

Abstract: Abstract. Multiwavelength observations of gamma-ray burst afterglows are presented, in particular those in the optical and millimetre wavelengths. I will focus on the observations mostly carried out at Spanish ground-based observatories (mainly the 10.4m GTC) and at the Plateau de Bure Interferometer in the French Alps. The importance of global networks of robotic telescopes (like BOOTES, established worldwide) for early time observations in order to put constraints on the physical mechanisms of the GRB early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…However, further investigations over radio, optical, and X-ray bands are needed to specifically address the reason of radio lead for this atypical outburst. -Tirado et al (1992) discovered GRS 1915+105 using WATCH on board GRANAT satellite. Apparent superluminal jets were detected (Mirabel & Rodríguez (1994)).…”
Section: H 1743-322mentioning
confidence: 99%
“…However, further investigations over radio, optical, and X-ray bands are needed to specifically address the reason of radio lead for this atypical outburst. -Tirado et al (1992) discovered GRS 1915+105 using WATCH on board GRANAT satellite. Apparent superluminal jets were detected (Mirabel & Rodríguez (1994)).…”
Section: H 1743-322mentioning
confidence: 99%
“…GRS 1915+105 has been active since its discovery in 1992 (Castro-Tirado et al 1992) and has become one of the best studied Galactic BHBs. The source shows complex timing and spectral properties that are quite different from other BHBs (except for IGR J17091−3624, Altamirano et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…At this precise location, an IR counterpart was reported (Mirabel et al 1993b, Castro-Tirado et al 1993, which was later confirmed by means of near-IR spectroscopy, showing variable, non Doppler-shifted emission lines, with the system suggested to be a low-mass X-ray binary (LMXB) (Castro-Tirado et al 1996), which was finally confirmed in 2001. See also Fig.…”
Section: The Discoverymentioning
confidence: 83%